Developmental ability of Hanwoo muscle satellite cells under culture conditions mimicking the in vivo environment - Park, Gyutae; Park, Sanghun; Oh, Sehyuk; Lee, Sol-Hee; Choi, Jungseok (Frontiers in Sustainable Food Systems, 2024)
Cultivated meat refers to edible meat obtained by proliferating cells without killing livestock in a laboratory. Selection of donor animals is a crucial factor for efficient cell culture production. Hanwoo is a native Korean taurine cattle breed raised as livestock in Korea since before 2000 B.C. Cells isolated from Hanwoo, which has little genetic diversity, are expected to be advantageous in cell culture because of the existence of less individual difference. However, cells collected from Hanwoo are in a state where efficient culture conditions have not been established. Therefore, in this study, we investigated effects of mimicking in vivo environment on proliferation and differentiation of Hanwoo muscle satellite cells. Culture conditions consisted of CON (37°C/20% O2), T1 (37°C/2% O2), T2 (39°C/20% O2), and T3 (39°C/2% O2). Cell numbers decreased and expression levels of PAX7 and MYF5 decreased at a temperature of 39°C (p < 0.05). Conversely, 2% oxygen increased the number of cells and expression levels of PAX7 and MYF5 (p < 0.05). A temperature of 39°C inhibited the proliferation of Hanwoo muscle satellite cells by reducing expression of PAX7 and MYF5 (p < 0.05). Conversely, 2% oxygen promoted the proliferation of Hanwoo muscle satellite cells by enhancing expression of PAX7 and MYF5 (p < 0.05). During differentiation, a temperature of 39°C improved myotube area and fusion index (p < 0.05). RT-qPCR and western blotting results unveiled that a culture temperature of 39°C increased expression levels of MYH2 gene and DES and MYOG proteins (p < 0.05). Additionally, an interactive condition increased expression levels of MYOD1, DES, and MYOG genes (p < 0.05). These results indicated that a temperature of 39°C promoted differentiation of Hanwoo muscle satellite cells by increasing DES and MYOG protein expression. Thus, production of cultivated meat using Hanwoo muscle satellite cells is expected to be efficient under 2% oxygen for proliferation and 39°C for differentiation.